Edisi 1 Vol 2 September 2023 MEMBANGUN UMAT DENGAN ZAKAT: PENGELOLAAN ZAKAT PADA ERA NABI DAN KHULAFAURRASYIDIN - mazidatul, fina (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2023)
Zakat in history is refferd to the first social institution in Islam. Its management also changes from time to time along with the development of the times. Starting from the period of the prophet when in Mecca, Medina and during the khulafaurrashiddin. By reopening at the dynamic management of zakat in the past, we can take lessons so that the management of zakat in Indonesia over time also makes progress so that the goals and functions of zakat are achieved.